Analisis Kepuasan Gen Z terhadap Shopee PayLater dengan Metode User Experience Questionnaire - Matthew Atmaja; Endang Haryani (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This study aims to analyze Gen Z’s satisfaction, which are students of Satya Wacana Christian University, on Shopee PayLater (SPL) based on user experience. This research is driven by the increase in e-commerce transactions and digital financial technology use with Buy Now Pay Later method among Gen Z. This research applies a quantitative descriptive approach with the User Experience Questionnaire method. After completing the survey and analysis, this research found that Gen Z's experience of SPL showed an average of 1.66 out of 3.00 or at the Good level. Thus, this study concludes that Gen Z is satisfied with SPL services. All variables contribute to satisfaction. The Perspecuity or Clarity gave the best experience to students at a score of 2.00 or Excellent level, supported by strong experiences on the Efficiency and Dependability. Significant satisfaction on these three factors influences the strength of Pragmatic Quality which provides the highest satisfaction of 1.76. Thus, Gen Z is most satisfied with SPL because of its practical ability, clarity and convenience. While the Hedonic Quality of the Stimulation and Novelty, as well as the Attractiveness had a positive influence on Gen Z's satisfaction, it had the lowest score among others, especially from the aspect of SPL's ability to motivate its users (0.9).